2017
DOI: 10.3892/ol.2017.6427
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 expression is associated with poorer prognosis and high recurrence in urothelial bladder cancer

Abstract: Abstract. The aim of the present study was to investigate the clinical significance of TNF receptor-associated factor 6 (TRAF6) expression in urothelial bladder cancer. TRAF6 expression was detected by immunohistochemistry in 126 samples of patients with urothelial bladder cancer. The association between clinicopathological factors and TRAF6 expression was analyzed by χ 2 test. The association between TRAF6 expression, overall survival rate and the recurrence-free survival rate was evaluated in univariate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has been also implied that activation lymphotoxin β receptor (LTβR) could result in inflammation‐induced carcinogenesis via upregulation of TNF‐α expression (Shen, Zhou, Zhou, Zhou, & Lin, ). In another study, increased expression of TNF receptor‐associated factor 6 (TRAF6) has been observed in urothelial bladder carcinoma patients and it has been concluded that TRAF6 could lead to the tumor invasion and is an independent factor of relapse/prognosis (H. Wu et al, ). Moreover, Zirakzadeh et al () reported that the effectiveness of doxorubicin in the treatment of BC was partly through downregulation of TNF‐α.…”
Section: Proinflammatory and Anti‐inflammatory Cytokines In Bcmentioning
confidence: 99%
“…It has been also implied that activation lymphotoxin β receptor (LTβR) could result in inflammation‐induced carcinogenesis via upregulation of TNF‐α expression (Shen, Zhou, Zhou, Zhou, & Lin, ). In another study, increased expression of TNF receptor‐associated factor 6 (TRAF6) has been observed in urothelial bladder carcinoma patients and it has been concluded that TRAF6 could lead to the tumor invasion and is an independent factor of relapse/prognosis (H. Wu et al, ). Moreover, Zirakzadeh et al () reported that the effectiveness of doxorubicin in the treatment of BC was partly through downregulation of TNF‐α.…”
Section: Proinflammatory and Anti‐inflammatory Cytokines In Bcmentioning
confidence: 99%
“…The knockdown of PKCζ in three different prostate cancer cell lines in vivo leads to a reduction in tumor growth and metastasis [57]. The role of TRAF6 as an oncogene in cancer has recently emerged, as TRAF6 is amplified in several types of cancer, such as lung carcinoma [58], advanced prostate cancer [59], gastric carcinoma [60] and bladder cancer [61], and promotes angiogenesis and glioblastoma progression [62,63]. For further reading about the oncogenic role of TRAF6 in cancer, see a recent review [64].…”
Section: Tgf-β Signals Are Transduced By Canonical and Non-canonical ...mentioning
confidence: 99%